Moderating Effect of Good Corporate Governance on Financial Distress in Indonesia Stock Exchange - bobby; Jonnardi (JURNAL AKUNTANSI DAN BISNIS : Jurnal Program Studi Akuntansi, 2023)
Financial Distress is a process of financial distress felt by an entity before bankruptcy occurs. There are two theories that underlie the conceptual framework in this study, namely agency theory and signaling theory. The research aims to obtain empirical clues about the effects of sales growth, liquidity, firm size on financial distress with moderation of good corporate governance in manufacturing entities listed on the Indonesia Stock Exchange (IDX) for the period 2017 - 2021. There were 63 samples of manufacturing companies used in the study using the purposive sampling method. The study used secondary data, namely financial statements. In testing hypotheses using statistical methods, namely panel data regression analysis models. The results showed that sales growth has an insignificant influence, liquidity has a significant positive influence, firm size has a significant negative influence, while good corporate governance cannot moderate the influence of sales growth, but successfully moderates the effect of liquidity and firm size on financial distress.